The Effect of Brainstorming-Assisted ARCS Model on Students' Critical Thinking Skills in Alternative Energy Concept - Fauziah, Fuzi; Makiyah, Yanti Sofi; Suhendi, Herni Yuniarti (Department of Physics Education, Universitas Mataram, 2025)
Critical thinking skills are important in learning because they encompass conceptual understanding and rational decision-making. However, students' critical thinking skills are relatively low, and innovation in physics learning is minimal. Therefore, the ARCS model, supported by brainstorming, was implemented as an intervention. The study aims to identify the effect of the Attention, Relevance, Confidence, Satisfaction learning model assisted by brainstorming on students' critical thinking skills on alternative energy material in class X of SMA Negeri 1 Cihaurbeuti in the 2024/2025 academic year. The methodological design used is a quasi-experiment with a posttest only control group design structure. The study population includes 12 classes of class X, with purposive sampling of two classes, namely X-6 and X-8. The research measurement instrument is an instrument in the form of a descriptive assessment consisting of six questions arranged to represent all indicators of critical thinking skills. Hypothesis test analysis using the t-test produces a value of which significantly exceeds the critical threshold of at the significance level ( =0.05) thus stating that H₀ is rejected. Thus, the Attention, Relevance, Confidence, Satisfaction model assisted by brainstorming provides a significant contribution to students' critical thinking skills. This study recommends learning using the ARCS model combined with brainstorming methods to improve critical thinking skills and encourage student involvement in formulating ideas or solutions to problems collaboratively. Further research could empirically test the effectiveness of the combination of ARCS and brainstorming on different topics or with variations of other collaborative strategiesCritical thinking skills are important in learning because they encompass conceptual understanding and rational decision-making. However, students' critical thinking skills are relatively low, and innovation in physics learning is minimal. Therefore, the ARCS model, supported by brainstorming, was implemented as an intervention. The study aims to identify the effect of the Attention, Relevance, Confidence, Satisfaction learning model assisted by brainstorming on students' critical thinking skills on alternative energy material in class X of SMA Negeri 1 Cihaurbeuti in the 2024/2025 academic year. The methodological design used is a quasi-experiment with a posttest only control group design structure. The study population includes 12 classes of class X, with purposive sampling of two classes, namely X-6 and X-8. The research measurement instrument is an instrument in the form of a descriptive assessment consisting of six questions arranged to represent all indicators of critical thinking skills. Hypothesis test analysis using the t-test produces a value of which significantly exceeds the critical threshold of at the significance level ( =0.05) thus stating that H₀ is rejected. Thus, the Attention, Relevance, Confidence, Satisfaction model assisted by brainstorming provides a significant contribution to students' critical thinking skills. This study recommends learning using the ARCS model combined with brainstorming methods to improve critical thinking skills and encourage student involvement in formulating ideas or solutions to problems collaboratively. Further research could empirically test the effectiveness of the combination of ARCS and brainstorming on different topics or with variations of other collaborative strategies.